New Challenges in Computational Collective Intelligence - Nguyen, Ngoc Thanh.; Katarzyniak, RadosBaw Piotr.; Janiak, Adam. (Studies in Computational Intelligence, 2009)
The book consists of 29 chapters which have been selected and invited from the submissions to the 1st International Conference on Collective Intelligence - Semantic Web, Social Networks & Multiagent Systems (ICCCI 2009). All chapters in the book discuss various examples of applications of computational collective intelligence and related technologies to such fields as semantic web, information systems ontologies, social networks, agent and multiagent systems. The editors hope that the book can be useful for graduate and Ph.D. students in Computer Science, in particular participants to courses on Soft Computing, Multi-Agent Systems and Robotics. This book can also be useful for researchers working on the concept of computational collective intelligence in artificial populations. It is the hope of the editors that readers of this volume can find many inspiring ideas and use them to create new cases intelligent collectives. Many such challenges are suggested by particular approaches and models presented in particular chapters of this book.